Yamal Multi-Field Cooperation in 1930s-1950s: Historical Review - V. V. Aksarin (Научный диалог)
The history of formation of multi-field cooperation of Yamal is investigated. On the basis of the first introduced into scientific circulation archival materials of the State institution “State archive of the Yamalo-Nenets Autonomous Okrug” the organizational and legal issues of creation of the Northern cooperation, separate industrial artels working in the system of the Yamal-Nenets multi-field Union of cooperatives are considered. The author attempts to comprehend the history of cooperation, the role of leaders and their participation in its activities. The characteristic features of the Northern and multi-field cooperation of Yamal, in particular, in contrast to its other types, were the late creation and registration in an independent Union, the frequent change of managerial personnel, weak material and technical support and loose labour discipline, geographical and transport distance, severe climatic conditions of the North of Western Siberia. Archival data allowed to trace the history of the formation and development of commercial cooperation, its transformation and problems that had to be faced during the 1930s-1950s. Evidence is given that during the period of activity of multi-field cooperation of Yamal one had to experience financial and logistical difficulties. The article fills a gap in the history of the origin, formation and development of cooperation in the North of Western Siberia.